An Experimental Investigation on the Flow Properties of Bulk Solids - Rohilla, Lokesh (My University, 2016)
This thesis results from an ongoing investigation on the effects of powder physical properties on flow properties of fine powders. Seven fly ash samples (F type, median particle size 139μm-21μm; particle density 2013-2015 Kg/m3; bulk density 670.2 Kg/m3-794.9 Kg/m3) were collected directly from electrostatic precipitator hoppers (ESP hopper) corresponding to seven ESP fields. Their powder flow properties were measured by using Brookfield Powder Flow tester. It was found that fly ash samples collected from first four stages were easy flowing and fly ash samples collected from later stages were of cohesive nature according to Jenike (1964) classification. Transition particle size which caused change in flow properties of fly ash was found experimentally. Transition particle size was identified by using flowability classification and compaction dynamics. Transition in flow behaviour was probably due to large magnitude of inter-particle forces among powder particles as compared to weight of the particle. All powder flow properties like cohesion, unconfined yield strength etc showed asymptotic behaviour after transition particle size. Additionally, twenty two fly ash samples (median particle size 139μm - 4μm; particle density 2960 - 2013 Kg/m3; bulk density 794.9 Kg/m3- 494.3Kg/m3) of different flowability were evaluated for their feasibility to flow from an ESP hopper of specified dimensions. It was found that only easy flowing fly ash samples can flow reliably from ESP hopper under gravity while cohesive and very cohesive fly ash samples will require discharge aids. A qualitative idea about magnitude of aeration rate necessary has been given on the basis of minimum fluidisation velocity and permeability factor. It was observed that all fly ash samples do not require same aeration rate which is generally the practice in industries. A new cohesion model has been developed by using only powder physical properties. The new model eliminates the need of conducting shear testing of fine powders to find cohesion and gives 20% more accuracy as compared to existing cohesion models. Finally, a new model for unconfined yield strength has been proposed which can be used to rank powders according to their flowability without conducting their shear testing.
Keywords: Bulk solids; flow properties